LIGNIN VALORIZATION IN BIOREFINERY CONCEPT (II) - Gutiérrez Villanueva, Aixa R.; Guirola Céspedes, Claudia; de Armas Martínez, Ana Celia; Albernas Carvajal, Yailet; Villanueva Ramos, Gretel (Centro Azúcar Journal, 2020)
Introduction: There are several types of lignin and, among them, which derives from processes that use organic solvents in the presence of catalyst, acid or basic has less environmental impact with respect to conventional ones since organic solvents are easily recovered by distillation, also this type of lignins, has specific uses because its structure. Hydrolysis of sugarcane bagasse produces lignin-rich currents that can be integrated into the biorefinery concept. Objective: Demonstrate the economic feasibility of integrating the lignin production process into the biorefinery concept based on its characteristics and the knowledge of its producers at the international level. Materials and methods: A search (briefing) that provides useful data for the development of the lignin obtaining process is carried out, based on this process is integrated into the concept of biorefinery and its economic indicators are determined. Results and Discussion: The applications of lignin as a result of bagasse hydrolysis can be: the elaboration of carbon fibers, vanillin, and in the production of phenol derivatives. By assessing the feasibility of investment in the biorefinery scheme with the integration of lignin, dynamic profitability indicators are obtained that demonstrate the feasibility of the proposal, maintaining the recovery of investment in 5.2 years as de Armas, (2019). Conclusions: The proposed process is justified with the applications of lignin and can be integrated into the biorefinery while maintaining its profitability.